Classification of Audio Segments using Voice Activity Detection - Kaur, S; Mittal, P. (International Journal of Computer Sciences and Engineering, 2020)
Voice activity detection is classifying speech and non-speech frames. Effectively working and noise tolerant voice activity detection technique is responsible for better performance of many new speech technologies in the area of speech processing. In this paper, an unsupervised method for VAD is proposed to identify the segments of speech- presence and speech-absence in an audio. To make the presented algorithm effective and computationally fast, it is implemented by using long-term parameters that are extracted by using Petrosian algorithm used for fractal dimensions. This system plays a significant role in terms of achieving improved speech quality. Two types of datasets recorded in English and Arabic languages are used to analyses the output of the proposed algorithm. An Array of 85 audio signals of TIMIT Database, of different Signal to noise ratios is tested using the algorithm at once. The evaluated performance suggested that the proposed algorithm identifies segments in the audios with different SNR’s.